Analysis of damage caused by siloxanes in stationary reciprocating internal combustion engines operating with landfill gas. (April 2015) - Álvarez-Flórez, Jesús; Egusquiza, Eduard
Highlights: The main types of damage found in ICE using landfill gas have been studied. Combustion of fuel with siloxanes produces two types of residues. Residues attach to combustion chamber surfaces reducing the heat transfer. Residues also attach to piston ring grooves causing lubrication problems. A method to prevent damage based in engine oil IR analysis is presented. Abstract: Failures in reciprocating internal combustion engines operating with landfill gas are not uncommon. In general, damage is located in the combustion chamber surfaces and in the ring grooves, where a layer of non-volatile combustion products is deposited. These deposits attached to the surfaces reduce heat transfer and increase inner temperature, which produces a knocking phenomena damaging the crank bearings and fusing of the piston head material. Lubrication problems also appear due to the formation of a layer of soft paste silicone deposits in the rings grooves, which increases friction losses and accelerates wear on cylinder and rings. In this paper, some typical examples of damaged engines are presented. The deposits found were analysed using Scanning Electron Microscope and Energy Dispersive X-ray Spectroscopy (SEM–EDX). Additionally, the engine oil used was also analysed by Infra-Red Spectrometry (IR) and the results were compared with known organo-compounds. A method to detect incipient failure caused by organo-compounds contained in landfill gas is introduced. Silica appears in the layers covering the combustion chamber, as well as silicone compound in the top cylinder zone, piston and ring grooves. Damage is associated with siloxanes (organo-silicon compounds) contained in the landfill gas, which decompose in the combustion chamber, generating silicic acid and formaldehyde under the high temperature conditions throughout the combustion processes.